Game theory - Maschler, Michael; Solan, Eilon; Zamir, Shmuel (New Delhi Cambridge University Press, 2020)
Game theory is the mathematical study of strategic decision-making, analyzing how rational individuals (players) interact in situations (games) where their outcomes depend on each other's choices, applying to everything from chess and business competition (pricing) to politics and biology.